Penerapan C&C Learning Untuk Meningkatkan Motivasi dan Kemampuan Akademik Mahasiswa FKIP Bahasa Inggris Universitas Kanjuruhan dalam Matakuliah Reading Comprehension - Muhaji, Uun (Jurnal Inspirasi, 2014)
The objective of this research is to improve studentsâ motivation and achievement in Reading Comprehension class through C&C Learning. Combining cooperative and competitive activities in Reading Comprehension course was really helpful in creating more joyful learning. The students were enthusiastic to comprehend the texts because they were going to use them in a competition among their groups. They became more active and showed more interest in the course. There had been an atmosphere of enjoyment and enthusiasm in the class since they experienced the combination of cooperative and competitive activities for the Reading Comprehension course. The result showed that the class was dynamic and alive, thus studentsâ motivation was increased. Furthermore, studentsâ achievement wasalso significantly improved. Â Kata Kunci: C&C Learning, CAR, Â Reading Comprehension